2014
DOI: 10.1049/iet-nbt.2013.0059
|View full text |Cite
|
Sign up to set email alerts
|

Green rapid biogenic synthesis of bioactive silver nanoparticles (AgNPs) using Pseudomonas aeruginosa

Abstract: The present work was focused on isolating a bacterial strain of Pseudomonas sp. with the ability to synthesise AgNPs rapidly. A strain of Pseudomonas aeruginosa designated JO was found to be a potential candidate for rapid synthesis of AgNPs with a synthesis time of 4h in light, at room temperature which is a shorter time period noticed for the synthesis when compared to the previous reports Biosynthesis of AgNPs was achieved by addition of culture supernatant with aqueous silver nitrate solution (1 mM). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…1 ) , indicated a surface plasmon resonance (SPR), having nanoparticles with sizes less than 100 nm. This could be due to excitation of electrons in the conductive band around the nanoparticles surface as reported by Busi et al ( 2014 ).
Fig.
…”
Section: Resultsmentioning
confidence: 71%
“…1 ) , indicated a surface plasmon resonance (SPR), having nanoparticles with sizes less than 100 nm. This could be due to excitation of electrons in the conductive band around the nanoparticles surface as reported by Busi et al ( 2014 ).
Fig.
…”
Section: Resultsmentioning
confidence: 71%
“…The biopolymer forms a ligand-shell surrounding AgNPs at the core, forming a silver polymer core-shell structure. The polymeric shell decreases the surface potential that is responsible for accumulation of the silver nanoparticles to larger aggregates (Busi et al, 2014). Frequently, microbes are considered dead when they cannot be cultured.…”
Section: Discussionmentioning
confidence: 99%
“…Many bacteria have been shown to produce AgNPs when exposed to light, and some require light to occur. (68,70,72,78,108,111,113) Wei et al (140) have demonstrated that solar radiation intensity influenced the biosynthesis of nanoparticles in CFE. Sunlight caused the reaction rate to increase in an intensity-dependent manner.…”
Section: Visible Lightmentioning
confidence: 99%